Risk of Recurrence in Women With Bipolar Disorder During Pregnancy: Prospective Study of Mood Stabilizer Discontinuation - Viguera, Adele C.; Whitfield, Theodore; Baldessarini, Ross J.; Newport, D. Jeffrey; Stowe, Zachary; Reminick, Alison; Zurick, Amanda; Cohen, Lee S. (The American journal of psychiatry, 2007)
Objective: This study estimated the risk of recurrence of mood episodes among women with a history of bipolar disorder who continued or discontinued treatment with mood stabilizers during pregnancy. Method: In a prospective observational clinical cohort study, the authors determined recurrence risk and survival-analysis-based time to recurrence of a new episode in 89 pregnant women with DSM-IV bipolar disorder. Eligible subjects were euthymic at conception and continued mood stabilizer treatment or discontinued treatment proximate to conception. Results: The overall risk of at least one recurrence in pregnancy was 71%. Among women who discontinued versus continued mood stabilizer treatment, recurrence risk was twofold greater, median time to first recurrence was more than fourfold shorter, and the proportion of weeks ill during pregnancy was five times greater. Median recurrence latency was 11 times shorter after abrupt rapid versus gradual discontinuation of mood stabilizer. Most recurrences were depressive or mixed (74%), and 47% occurred during the first trimester. Predictors of recurrence included bipolar II disorder diagnosis, earlier onset, more recurrences year, recent illness, use of antidepressants, and use of anticonvulsants versus lithium. Conclusions: Discontinuation of mood stabilizer, particularly abruptly, during pregnancy carries a high risk for new morbidity in women with bipolar disorder, especially for early depressive and dysphoric states. However, this risk is reduced markedly by continued mood stabilizer treatment. Treatment planning for pregnant women with bipolar disorder should consider not only the relative risks of fetal exposure to mood stabilizers but also the high risk of recurrence and morbidity associated with stopping maintenance mood stabilizer treatment.